Job Satisfaction and Turnover Intention among Malaysian Private University Academics: Perceived Organisational Support as a Moderator - Orpina, Septriyan; Abdul Jalil, Nurul Iman Binti; Ting, T'ng Soo (The South East Asian Journal of Management, 2022)
Research Aims: The present research examines the extent to which job satisfaction predicts turnover intentions and examines the extent to which perceived organisational support moderates the association between job satisfaction and turnover intention among academics in Malaysian private universities. Design/Methodology/Approach: This research adopted a quantitative method. The Turnover Intention Scale (TIS-6), Minnesota Satisfaction Questionnaire (MSQ), and Survey of Perceived Organisational Support (SPOS) questionnaires were administered. Multistage cluster random sampling was used in this study. A total of 327 respondents provided valid data and analysed it using SPSS Process Macro Version 3.5. Research Findings: Job satisfaction was found to be a negative predictor of turnover intention. The association between job satisfaction and turnover intention was shown to be moderated by perceived organisational support. Theoretical Contribution/Originality: The finding validated that perceived organisational support moderates the association between job satisfaction and turnover intention and demonstrates that academicians who perceive their organisation to be caring and supportive of their well-being will be more satisfied and less likely to intend to leave their organisational setting. Managerial Implication in the South East Asian context: The study provides an excellent platform for university managers to use in designing organisational support systems, including job structure, environment, autonomy, or flexibility to reduce academicians’ turnover intention and to increase academician’s job satisfaction. Research Limitation & Implications: The causal relationships between variables are a limitation of current research. This research provides valuable information for future researchers as well as raises awareness among academic staff about factors related to turnover intentions.